Work Value pada Guru Ditinjau dari Budaya Etnis Flores - Sitti Anggraini; Xaveria Gereina Kapuka (Departement of Mathematics Education, 2022)
This study aims to determine differences in teacher work values ​​in terms of Flores ethnic culture. The subjects in this study totaled 120 teachers spread across five Flores ethnicities, namely the Manggarai, Bajawa, East Flores, Ende Lio, Sikka Krowe ethnicities. This type of research uses a comparative quantitative research approach. The results showed that there were differences in teacher work values ​​in terms of Flores ethnic culture, with the results of the hypothesis test (t test) showing 0.000 ˂ 0.05, it can be seen that the significant results are less than 0.05. In addition, the results of this study also show that the highest work value is in the Manggarai ethnic group, with a mean of 102.29, followed by the Bajawa ethnic group, with a mean of 100.29, then the East Flores ethnic group, with a mean of 99.44 and the Ende-Lio ethnic group, with a mean of 98.78. and the lowest work value for the Sikka-Krowe ethnic group with a mean of 98.12.